2007
DOI: 10.1021/bm0609691
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Gastric Mucin Exhibits a pH-Dependent Sol−Gel Transition

Abstract: Gastric mucin, a high molecular weight glycoprotein, is responsible for providing the gel-forming properties and protective function of the gastric mucus layer. Bulk rheology measurements in the linear viscoelastic regime show that gastric mucin undergoes a pH-dependent sol-gel transition from a viscoelastic solution at neutral pH to a soft viscoelastic gel in acidic conditions, with the transition occurring near pH 4. In addition to pH-dependent gelation behavior in this system, further rheological studies un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
282
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 275 publications
(313 citation statements)
references
References 49 publications
27
282
1
3
Order By: Relevance
“…Although pH remained constant in control samples over the period of incubation, in the presence of H. pylori, the pH rapidly elevated to 7.1 to 7.4. In addition to the measured change in pH, we found that there was also a profound difference in the rheological response of the two samples in a manner that was strikingly consistent with that observed in the pH 4 (gel) and pH 6 (solution) buffered PGM samples previously published (26). Frequency dependent viscoelastic moduli (Fig.…”
Section: H Pylori Elevates Ph and Reduces Bulk Vscoelasticity In Gassupporting
confidence: 89%
See 4 more Smart Citations
“…Although pH remained constant in control samples over the period of incubation, in the presence of H. pylori, the pH rapidly elevated to 7.1 to 7.4. In addition to the measured change in pH, we found that there was also a profound difference in the rheological response of the two samples in a manner that was strikingly consistent with that observed in the pH 4 (gel) and pH 6 (solution) buffered PGM samples previously published (26). Frequency dependent viscoelastic moduli (Fig.…”
Section: H Pylori Elevates Ph and Reduces Bulk Vscoelasticity In Gassupporting
confidence: 89%
“…1B), reveal the characteristic yield stress and ''weak strain overshoot'' as described by Hyun et al (32), in the control sample. However, this behavior has completely vanished in the sample with H. pylori which, like the previously published pH 6 (solution) sample, has a very limited linear response regime below 0.1 Pa (26). Finally, the dramatic loss of viscosity and diminishing of shear thinning behavior because of H. pylori observed in steady shear experiments (Fig.…”
Section: H Pylori Elevates Ph and Reduces Bulk Vscoelasticity In Gassupporting
confidence: 74%
See 3 more Smart Citations